Hybrid Technology Internalisation Strategies in Industrial Services: The Case of Foam Pigging - Levina Marchyani; Raden Aswin Rahadi (Integrasi Sains Media, 2026)
Technology acquisition in specialised industrial services often fails to translate into internal capability when knowledge remains externalised. In Indonesia, foam pigging technology remains sourced from external actors, despite growing local content requirements and strategic interest in industrial independence. This study examines the case of PT BES by applying the Resource-Based View (RBV) and Knowledge-Based View (KBV) to assess internalisation pathways. Using a mixed-method approach, the study combines SWOT analysis and discounted cash flow modelling—covering Net Present Value (NPV), Internal Rate of Return (IRR), and Cash-on-Cash (CoC) returns—to evaluate two options: talent acquisition (TA) and joint venture (JV). Results show that while both approaches are financially viable, TA enables early control and learning, whereas JV offers long-term expansion with shared risk. The proposed hybrid sequence—TA followed by JV—supports gradual internal capability formation. This case contributes to technology management literature by demonstrating how hybrid strategies can resolve the tension between knowledge dependence and capability development under regulatory constraints.